Податкове регулювання соціального захисту населення - Насібова, Ольга Вікторівна (Заклад вищої освіти "Міжнародний університет бізнесу і права", 2018)
У статті досліджено механізм податкового регулювання соціального захисту населення в Україні. Проаналізовано загальні податкові надходження та прибуткове оподаткування за 2001–2017 роки. Визначено податкове навантаження на громадян з урахуванням єдиного соціального внеску, розраховано ефективну ставку оподаткування доходів населення. Запропоновано рекомендації щодо підвищення регулятивного потенціалу обов’язкових платежів як дже рела фінансового забезпечення соціального захисту населення

he fundamental basis for social welfare system is a financial security social protection, which involves creating conditions for the reproduction and development of human capi tal, which requires the formation of effective mechanisms of regulation of distribution relations aimed at harmon ing the interests of economy and society. Reduced quality of life and significant population stratification Ukraine by income level requires balanced approach to the collection of tax on personal income and payment of the single social contribution as the main instruments for regulating incomes and thorough analysis of the tax burden and its distribution to all segments of the population. Purpose. Assessment of the impact of tax regulation of social protection in terms of transformations and defining methodological approaches to the implementation of the regulatory potential income tax given a single social contribution. Methods. Dialectical cognition and structural techniques used for disclosure of the formation mechanism of tax regulation of social protection in the economic transformation; methods of analysis, synthesis, induction and deduction – to determine the characteristics of the formation of tax revenues, income tax on the basis of a single social contribution; methods analogy, comparison and statistical – to identify effective rate of income tax. Results. Analysis of total tax revenue and income tax for the years 2001–2017 showed the importance of tax instruments and leverage to reduce inequalities in income distribution and property of the society. The total tax burden as a factor of production “work” forms a single social contribution, along with taxes and fees on personal income and mitigate social inequality – tax incentives, using which the state provides certain parameters of the social system, enabling the play and develop. Conclusion. A tax adjustment mechanism of social protection of the state has the ability to affect the distribution cost proportion of gross domestic product for the welfare of the population. Excessive tax burden is a negative factor in the emergence of social tensions and the general impoverishment.
Tax regulations social protection
Keywords: податкове регулювання; податкові важелі; податкове навантаження; податок на доходи; єдиний соціальний внесок; соціальний захист; tax regulations; tax levers tax burden; income tax; single social tax; social security